2007
DOI: 10.1007/s10668-007-9135-y
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the attitudes of the inhabitants of Northern Karpathos, Greece: towards a framework for ecotourism development in environmentally sensitive areas

Abstract: This paper is a case study that sets out to explore the extent to which the local residents of the region of Northern Karpathos and Saria in the southeast corner of the Aegean have positive attitudes and perceptions towards ecotourism ventures for sustainable development. The area is included in the European Ecological Network Natura 2000 and was chosen for studying since it constitutes an ideal location for the promotion of soft and alternative forms of tourism. The investigation of the attitudes of the inhab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 51 publications
1
23
0
3
Order By: Relevance
“…Further, this might reflect a substantial change in local attitudes: after the intense park-people conflict during protected area designation (Papageorgiou & Brotherton, 1999), local spokespersons nowadays acknowledge environmentalist accounts. Analogous findings have been reported for other local communities within Greek protected areas (Bell et al, 2007;Hovardas & Korfiatis, 2008;Pipinos & Fokiali, 2007). The diffusion of the environmentalist discourse in rural areas can be attributed to the presence of environmental NGOs (WWF-Greece in our case), which can generate community engagement in environmental issues (Carmin, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…Further, this might reflect a substantial change in local attitudes: after the intense park-people conflict during protected area designation (Papageorgiou & Brotherton, 1999), local spokespersons nowadays acknowledge environmentalist accounts. Analogous findings have been reported for other local communities within Greek protected areas (Bell et al, 2007;Hovardas & Korfiatis, 2008;Pipinos & Fokiali, 2007). The diffusion of the environmentalist discourse in rural areas can be attributed to the presence of environmental NGOs (WWF-Greece in our case), which can generate community engagement in environmental issues (Carmin, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…A factor which may help in this is the development of ecotourism activities which are a possible means of self-sufficiency for protected areas (Dharmaratne et al, 2000;Pipinos and Fokiali, 2009). Eco-tourism may encourage people to support the protection of these areas.…”
Section: Discussionmentioning
confidence: 99%
“…In the study areas, agriculture is the main economic activity and thus the establishment of a protected area may lead to significant changes. A difference between the research areas concerns the level of development of tourist activities along with the involvement of external actors in environmental management which may also influence citizens' perceptions (Pipinos and Fokiali, 2009). …”
Section: Description Of Research Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Current and potential ecotourism activities may well serve to promote healthy nature conservation efforts in protected nature territories. Studies in several countries have shown that it can be achieved by proper notification that 52.6% of the local population have a positive perception of their area of natural and cultural protection measures that will ensure long-term economic viability, 81.6% are ready to attend the environmental education program, seeing it as a contribution to the development of ecotourism and its prosperity [12,9]. Protected area visitation is an important component of ecotourism, and, as such, must be sustainable.…”
mentioning
confidence: 99%